Accurate, explicit formulae for higher harmonic force spectroscopy by frequency modulation-AFM - Kuchuk, Kfir; Sivan, Uri (Beilstein Journal of Nanotechnology, 2015)
The nonlinear interaction between an AFM tip and a sample gives rise to oscillations of the cantilever at integral multiples (harmonics) of the fundamental resonance frequency. The higher order harmonics have long been recognized to hold invaluable information on short range interactions but their utilization has thus far been relatively limited due to theoretical and experimental complexities. In particular, existing approximations of the interaction force in terms of higher harmonic amplitudes generally require simultaneous measurements of multiple harmonics to achieve satisfactory accuracy. In the present letter we address the mathematical challenge and derive accurate, explicit formulae for both conservative and dissipative forces in terms of an arbitrary single harmonic. Additionally, we show that in frequency modulation-AFM (FM-AFM) each harmonic carries complete information on the force, obviating the need for multi-harmonic analysis. Finally, we show that higher harmonics may indeed be used to reconstruct short range forces more accurately than the fundamental harmonic when the oscillation amplitude is small compared with the interaction range.
Keywords: atomic force spectroscopy; higher harmonic FM-AFM

(untitled) - Fukuma, T.; Ueda, Y.; Yoshioka, S.; Asakawa, H. (Phys. Rev. Lett., 2010)

(untitled) - Herruzo, E. T.; Asakawa, H.; Fukuma, T.; Garcia, R. (Nanoscale, 2013)

(untitled) - Higgins, M. J.; Polcik, M.; Fukuma, T.; Sader, J. E.; Nakayama, Y.; Jarvis, S. P. (Biophys. J., 2006)

(untitled) - Loh, S.-H.; Jarvis, S. P. (Langmuir, 2010)

(untitled) - Garcia, R.; Herruzo, E. T. (Nat. Nanotechnol., 2012)

(untitled) - Giessibl, F. J. (Surf. Interface Anal., 2006)

(untitled) - Hembacher, S.; Giessibl, F. J.; Mannhart, J. (Science, 2004)

(untitled) - Wright, C. A.; Solares, S. D. (Nano Lett., 2011)

(untitled) - Santos, S.; Barcons, V.; Font, J.; Verdaguer, A. (Beilstein J. Nanotechnol., 2014)

(untitled) - Preiner, J.; Tang, J.; Pastushenko, V.; Hinterdorfer, P. (Phys. Rev. Lett., 2007)

(untitled) - Stark, R. W.; Heckl, W. M. (Rev. Sci. Instrum., 2003)

(untitled) - Sader, J. E.; Jarvis, S. P. (Appl. Phys. Lett., 2004)

(untitled) - Sader, J. E.; Uchihashi, T.; Higgins, M. J.; Farrell, A.; Nakayama, Y.; Jarvis, S. P. (Nanotechnology, 2005)

(untitled) - Giessibl, F. J. (Phys. Rev. B, 1997)

(untitled) - Dürig, U. (Appl. Phys. Lett., 1999)

(untitled) - Katan, A. J.; van Es, M. H.; Oosterkamp, T. H. (Nanotechnology, 2009)

(untitled) - Dürig, U. (New J. Phys., 2000)

(untitled) - Stark, M.; Stark, R. W.; Heckl, W. M.; Guckenberger, R. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Legleiter, J.; Park, M.; Cusick, B.; Kowalewski, T. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Sahin, O.; Quate, C.; Solgaard, O.; Atalar, A. (Phys. Rev. B, 2004)

(untitled) - Sahin, O.; Magonov, S.; Su, C.; Quate, C. F.; Solgaard, O. (Nat. Nanotechnol., 2007)

Handbook of Mathematical Functions - Milne-Thomson, L. M.; Abramowitz, M.; Stegun, I. A. (Dover, 1972)

(untitled) - Garcia, R.; Gómez, C. J.; Martinez, N. F.; Patil, S.; Dietz, C.; Magerle, R. (Phys. Rev. Lett., 2006)